2010
DOI: 10.1111/j.1600-051x.2010.01597.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of human periodontal ligament‐derived cells as a reliable source for cytotherapeutic use

Abstract: A protocol for the successful cultivation and validation of hPDL cells is proposed for clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
155
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 182 publications
(171 citation statements)
references
References 52 publications
12
155
1
3
Order By: Relevance
“…Taken together, the results of high periostin expression and a high ALP activity in hPDL cell sheets have confirmed evidence that cell sheets produced in CPC possess PDL properties. Furthermore, these results are consistent with those of experiments conducted on 41 samples of hPDL cells (Iwata et al 2010).…”
Section: Discussionsupporting
confidence: 94%
“…Taken together, the results of high periostin expression and a high ALP activity in hPDL cell sheets have confirmed evidence that cell sheets produced in CPC possess PDL properties. Furthermore, these results are consistent with those of experiments conducted on 41 samples of hPDL cells (Iwata et al 2010).…”
Section: Discussionsupporting
confidence: 94%
“…In particular, many preclinical and clinical studies have suggested that PDLSCs represent an effective therapeutic tool for periodontal regeneration (Bright et al 2015;Bassir et al 2016). In parallel, methods for PDLSC isolation and production are developing very quickly, from rapid and safe cell propagation/expansion (Iwata et al 2010;Jung et al 2013;Trubiani et al 2015;Wu et al 2016) to optimal cell material production (Wei et al 2012;Gao et al 2013;Iwata et al 2015). Nevertheless, major challenges still exist, particularly challenges related to producing large numbers of cells from clinically limited PDL tissues and manufacturing/banking robust cell materials, ideally in an off-the-shelf format Tang et al 2016;Wu et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Along with concerted efforts to produce predictable and reliable approaches to augment bone regeneration in intrabony bone defects, the development of tissue engineering and regenerative medicine has provided new avenues to improve the clinical outcomes of periodontal regeneration using stem cell-based technologies (Chen and Jin 2010;Izumi et al 2011;Chen et al 2012;Lu et al 2013;Monsarrat et al 2014). In this context, stem cells derived from the PDL (PDLSCs) have been demonstrated to be effective in preclinical trials and have been suggested as the best cell type for periodontal tissue regeneration (Iwata et al 2010;Dangaria et al 2011;Tsumanuma et al 2011;Dan et al 2014). Despite several small-scale pilot/feasibility studies that have been performed in humans (Feng et al 2010;Chen et al 2016), the clinical use of PDLSCs for periodontal regeneration still faces numerous challenges (Hynes et al 2012;Lu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The differentiation assay was performed as previously described [38]. To study osteogenesis, 1000 cells were plated in a 100-mm culture dish and cultured for 7 days.…”
Section: Differentiation Assaymentioning
confidence: 99%